Identifying Antioxidant and Antimicrobial Activities of the Phenolic Extracts and Mineral Contents of Virgin Olive Oils (Olea europaea L. cv. Edincik Su) from Different Regions in Turkey - Ayhan Dağdelen (Journal of Chemistry)
The objective of this study was to identify the antioxidant and antimicrobial activities of the phenolic extracts and mineral contents of virgin olive oils (Olea europaea L. cv. Edincik Su) obtained from three different locations, Edincik, Gomec, and Izmir, in Turkey. Antioxidant activity was analysed spectrometrically, antimicrobial effect was evaluated by disc diffusion method, and mineral contents were determined by using Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Total phenolic contents and free radical scavenging activities of Edincik Su olive cultivar were found between 159.99 and 189.64 mg gallic acid equivalent/kg and 21.76 and 31.79% inhibition of DPPH• radical values, respectively. Phenolic composition was also varied according to location and hydroxytyrosol and tyrosol were determined as major phenolic compounds. Fourteen pathogenic bacteria and two fungal strains were used to determine the antimicrobial activity. Phenolic extracts showed antimicrobial effect against a wide range of microorganisms and the descending rank of the antimicrobial activities was Gomec, Izmir, and Edincik samples. The highest antimicrobial activities were determined against Clostridium perfringens ATCC 13124 and Campylobacter jejuni ATCC  33291 in all samples. Sixteen elements were used as standards (eleven of them were heavy metals) to identify mineral contents. Fe, Mg, Sn, K, and Ca were determined in Gomec samples and Mg and K were detected in Edincik samples while no mineral content was detected in Izmir sample.